NIN—at the heart of NItrogen-fixing Nodule symbiosis - Shen, Lisha; Feng, Jian (Frontiers in Plant Science, 2024)
Legumes and actinorhizal plants establish symbiotic relationships with nitrogen-fixing bacteria, resulting in the formation of nodules. Nodules create an ideal environment for nitrogenase to convert atmospheric nitrogen into biological available ammonia. NODULE INCEPTION (NIN) is an indispensable transcription factor for all aspects of nodule symbiosis. Moreover, NIN is consistently lost in non-nodulating species over evolutions. Here we focus on recent advances in the signaling mechanisms of NIN during nodulation and discuss the role of NIN in the evolution of nitrogen-fixing nodule symbiosis. This is a provisional file, not the final typeset article RECEPTOR)/MtLYK3 (LysM RECEPTOR KINASE 3), LjNFR5/MtNFP (NOD FACTOR PERCEPTION), and LjSYMRK (SYMBIOTIC RECEPTOR LIKE KINASE)/MtDMI2 (DOSE NOT MAKE INFECTION), which form homomeric and heteromeric complexes on the plasma membrane of root hair cells, triggering the nitrogen-fixing symbiotic signaling pathway (Endre et al., 2002;